On the stability of inverter-based microgrids via LMI optimization - Trung, Truong Duc; Contzen, Miguel Parada (Journal of Computer Science and Cybernetics, 2015)
The implementation of a number of individual small distributed energy resources forms the new generation of power systems - the microgrid. For an isolated operating condition of microgrids, the classical stabilizing approaches for control of large power systems are no longer applicable, as the characteristics of microgrids differ significantly from conventional power systems. Therefore, a new control approach must be investigated in order to robustly stabilize microgrids during disturbances, which are caused by load changes and the intermittent nature of alternative energy sources. In the present paper, the stability of inverter-based microgrids is considered. A decentralized state-feedback control approach for inverter-based microgrids with a linear matrix inequality (LMI) stability condition is proposed. Controller gains for inverters are designed by solving the LMI optimization problem. The resulting controller stabilizes the system, guaranteeing zero steady-state frequency deviations. The control approach is then validated via an academical example.